Characterization of ocular biometrics and aqueous humor dynamics in primary angle closure suspects. Issue 7 (February 2017) - Guo, Li; Deng, Yuan; Fang, Li; Liu, Chaoqi; Guo, Tao
Abstract : Abstract: Detailed characterizations of ocular biometrics and parameters of aqueous humor dynamics are lacking in primary angle closure suspect (PACS) patients. This study aims to characterize these parameters and compare them with age-matched healthy volunteers. Elderly healthy volunteers (60.6 ± 7.2 years of age, mean ± SD, n = 28) and PACS patients (64.1 ± 11.6 years, n = 30) completed the study. Parameters investigated were axial length (AXL), anterior chamber depth (ACD), anterior chamber volume (ACV), central cornea thickness (CCT), intraocular pressure (IOP), aqueous flow (Fa), outflow facility (C), episcleral venous pressure (EVP), and uveoscleral outflow (Fu). Comparisons and correlations were made between and within groups. In healthy volunteers, ocular biometric parameters, IOP, and EVP correlated very well between the 2 eyes of each individual, but Fa, C, and Fu were not significantly correlated. Biometric parameters of the PACS group significantly ( P  < 0.001) differed from those of the healthy controls: AXL (23.31 ± 1.03 mm [PACS] vs 22.39 ± 1.04 mm [Control]; mean ± SD), ACD (2.44 ± 0.33 mm [PACS] vs 1.86 ± 0.25 mm [Control]), ACV (136.0 ± 36.1 μL [PACS] vs 81.4 ± 21.8 μL [Control]), CCT (526.9 ± 37.0 μm [PACS] vs 556.1 ± 28.4 μm [Control]). There was no significant change in IOP, Fa, C, EVP, or Fu between Control and PACS. Furthermore, IOP showed no significant correlations with AXL, ACD, ACV, CCT, or C in both groups. The PACS eyes had a shorter AXL, a shallower ACD, and a smaller ACV, but a thicker CCT. Despite these morphological changes, the PACS eyes did not have any significant changes in IOP, and aqueous humor dynamics parameters. This is consistent with the findings that IOP did not show significant correlations with biometrics, or C.